Analysis of Hearing Status in Patients with Type 2 Diabetes Mellitus - De, Dr. Sarmishtha (Innovative Journal of Medical and Health Sciences, 2015)
Introduction: The relation between hearing loss and diabetes mellitus appears as a controversial topic as different studies have given conflicting results. Present study aimed 1) To find the prevalence of SNHL in Type 2 DM 2) To study the association of hearing loss with the following factors among type 2 DM (a) Duration of DM , (b) Severity of hyperglycemia. 3) To evaluate the result of our study and to compare our data with similarly published studies. Methods: This Retrospective Analytical study involved data of 100 of the randomly selected patients ( candidates / study subjects) . ) It was noted and observed that Hearing tests like Pure tone audiometry and tympanometry were performed for all patients. For pure tone audiometry, thresholds were obtained by using modified Hughson – Westlake procedure. Results: . Prevalence of SNHL in type 2 DM was 79%. There was no association between SNHL and duration of DM but positive association was found between SNHL and severity of hyperglycemia. Conclusion: . In all type 2 DM while examining them clinically due consideration may be given to hearing tests along with other tests like Fasting and post prandial blood glucose levels (FBS, PPBS) and HbA1C level to find out the glycemic control. Also it is mandatory for necessary follow ups to be done regularly. Key Word : SNHL (Sensorineural hearing loss), Type 2 Diabetes Mellitus (DM), neuropathy, glucose levels.